CLOMIPHENE CITRATE STAIR STEP METHOD VERSUS TRADITIONAL METHOD FOR OVULATION INDUCTION IN PATIENTS WITH POLYCYSTIC OVARY SYNDROME: A RANDOMIZED CONTROLLED TRIAL (The Research of Medical Science Review, 2025)
Background: Polycystic ovary syndrome (PCOS) is the most common endocrine disorder of reproductive-aged women with a high incidence of anovulatory infertility. It is well known that clomiphene citrate (CC) is widely used as a first-line pharmacological agent for inducing ovulation. An alternative to the standard method, the “stair step” protocol escalates CC dose within the same cycle without waiting for a withdrawal bleed. The objective of this randomized controlled trial was to determine if the CC stairstep protocol is as efficacious as the conventional regimen in inducing ovulation as well as achieving pregnancy in women with PCOS. Methods: A total of 92 women aged 20–35 who have PCOS based on the modified Rotterdam criteria were randomly assigned equally to two groups. In the traditional method, the decrease in dose in subsequent cycles was done if ovulation was not achieved; however, such a decrease in dose was not done in Group A, as the dose was increased in subsequent cycles based on follicular response monitored by transvaginal ultrasound, and this dose was equal to 50 mg, 100 mg, 150 mg. Given expected ovulation rate difference of 25% between groups, the sample size calculation was performed based on a power of 80% and an alpha of 0.05. Ovulation induction at 12 weeks of amenorrhea and clinical pregnancy rate confirmed by serum β-hCG were the primary outcomes. Chi square tests were performed for categorical variables and independent t tests were used in the case of continuous variables. Results: The preliminary results showed greater ovulation rates in the stairstep group where the period to ovulation was decreased. Similar pregnancy rates were achieved once ovulation occurred, except that the stairstep protocol shortened the treatment period and thus favored it. Tables, bar graphs, and pie charts are presented and are detailed statistical analyses supported by them. Conclusion: However, this procedure prolongs the timing of ovulation, and therefore, does not follow the traditional ovulation induction manner, and thus is a promising, efficient alternative for ovulation induction in PCOS patients. These findings are recommended to be validated further through large-scale studies.